The Effect of Psychological Capital to Work-Life Balance for Married Female Police Officers - Rifdayanti Bakri; Rezky Ariany Aras; Suryadi Tandiayuk (Universitas Negeri Makassar, 2022)
As a member of the police, a female police officer is expected to work well and even with high professionalism, which means that in any situation, her tasks and responsibilities must be prioritized. However, this is certainly not easy for female police officers, especially those who are married or have families, automatically carrying out dual roles both in the workplace and in their family environment. Based on this, this study aims to determine the effect of psychological capital to work-life balance for married female police officers at the Mapolda X. This is a quantitative correlational study involving 203 married police officers. The results of this study show that psychological capital has a positive effect to work-life balance with an R2 value of 0.10, p<0.001. Based on the partial T test, it was also found that the aspects of self-efficacy and optimism had a positive effect on female police officers, while hope and resilience did not have a significant effect on WLB for married female police officer.